Role of Metabotropic Glutamate Receptors in Neurological Disorders - Crupi, Rosalia; Impellizzeri, Daniela; Cuzzocrea, Salvatore (Frontiers in Molecular Neuroscience, 2019)
Glutamate is a fundamental excitatory neurotransmitter in the mammalian central nervous system (CNS), playing key roles in memory, neuronal development, and synaptic plasticity.Moreover, excessive glutamate release has been implicated in neuronal cell death. There are both ionotropic and metabotropic glutamate receptors (mGluRs), the latter of which can be divided into eight subtypes and three subgroups based on homology sequence and their effects on cell signaling. Indeed, mGluRs exert fine control over glutamate activity by stimulating several cell-signaling pathways via the activation of G protein-coupled orG protein-independent cell signaling. The involvement of specific mGluRs in different forms of synaptic plasticity suggests that modulation of mGluRs may aid in the treatment of cognitive impairments related to several neurodevelopmental/psychiatric disorders and neurodegenerative diseases, which are associated with a high economic and social burden. Preclinical and clinical data have shown that, in the CNS, mGluRs are able to modulate presynaptic neurotransmission by fine-tuning neuronal firing and neurotransmitter release in a dynamic, activity-dependent manner. Currentstudies on drugs that target mGluRs have identified promising, innovative pharmacological tools for the treatment of neurodegenerative and neuropsychiatric conditions,including chronic pain.